Ventilative cooling potential of buildings in Australia. Issue 3 (September 2019) - Tartarini, F; Fiorentini, M; Ledo Gomis, L; Cooper, P
Abstract: The demand for space cooling is the fastest growing end-use of electricity in buildings since many rely on the use of air-conditioners only to control the indoor climate. Ventilative cooling is a passive cooling technique, which involves the use of outdoor air to lower buildings' indoor air temperature. In order to determine whether ventilative cooling may have the ability to reduce cooling loads, a detailed analysis of the local climate is needed. The aim of this study was to identify which Australian geographical regions have a suitable climate for the utilization of ventilative cooling techniques. The assessment of climatic potential for each geographic location was carried using two approaches: (i) a methodology which does not require detailed knowledge of the building characteristics, and; (ii) building performance simulation of a 'typical' Australian detached home. Results showed that the most populated Australian cities would benefit from the use of ventilative cooling techniques whereas the northern coastal region does not have a suitable climate.